Immobilization of metallporphyrins on polystyrene: efficient catalysts for aerobic oxidation of alcohols - Naik, R.; Joshi, P.; Deshpande, R. K. (Journal of Molecular Catalysis A-Chemical, 2005)
Metalloporphyrins of iron and cobalt have been successfully encapsulated for the first time using polystyrene matrix, exhibiting high activity for aerobic oxidation of alcohols mimicking cytochrome P-450 dependent mono oxygenases. This communication provides a simple and environmentally friendly protocol for immobilization of metalloporphyrins (MPs) on to polystyrenes in general, which gives stable,I reusable (see Footnote 1) and efficient catalysts for aerobic oxidation of alcohols. These catalysts were characterized by UV-vis as well as diffuse reflectance FT-IR spectroscopy. These catalysts not only have high turnover frequencies but also could be recovered quantitatively by simple filtration and reused without loss of activity. Considering their high dispersing capacity in organic solvents, they will definitely find broad spectrum of applications in the electronic as well as optical fields. This methodology will lead to a potential model to mimic the catalytic action of metalloporphyrins in the niche areas such as catalytic oxidations, drug metabolism, DNA cleavage, photodynamic therapy and many others. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: aerobic oxidation; Immobilization; metalloporphyrins; micro-encapsulation; Polystyrene; turnover frequency